Diagnostic Workup of Retroperitoneal Sarcoma in Bangladesh (Bioresearch Communications, 2026)
Background: Retroperitoneal sarcoma is a rare and heterogeneous malignancy that often presents late due to its deep anatomical location and nonspecific symptoms. Preoperative diagnosis relies on imaging and, ideally, tissue sampling, though diagnostic pathways may differ substantially in resource-limited settings. Methods: This case series included 28 adult patients with histologically confirmed retroperitoneal sarcoma managed between July 2021 and June 2022. Data on demographics, imaging findings, diagnostic intervals, biopsy utilization, and concordance of preoperative modalities with final histopathology were analyzed descriptively. Findings: The mean age was 45.4 ± 16.4 years, with a slight male predominance (57.1%). The median diagnostic delay was 45 days and the median preoperative interval was 17.5 days. Liposarcoma was the predominant histological subtype, accounting for 50.0% of cases, followed by undifferentiated pleomorphic sarcoma (14.3%) and leiomyosarcoma (10.7%). Tumors had a median imaging size of 12.5 cm, with adjacent organ involvement in 35.7% of cases and rare distant metastasis (3.6%). CT scan was performed in all patients, while preoperative tissue sampling was undertaken in only 32.1%. Concordance with the final histopathological diagnosis for broad identification of RPS was 85.7% (24/28) for CT impression, 57.1% (4/7) for FNAC, and 100.0% (2/2) for core needle biopsy; however, the latter finding should be interpreted cautiously because it was based on only two patients. Conclusion: In this resource-limited setting, CT remains the cornerstone of preoperative evaluation for retroperitoneal sarcoma, while preoperative tissue diagnosis is infrequently performed. Expanding access to core needle biopsy and reducing diagnostic delays may enhance diagnostic accuracy and preoperative planning.Bioresearch Commu. 12(2): 2102-2108, 2026 (January)